Constructionilsm of Functionlism: Belom Bahadat as Legal Culture of The Dayak Community In Palangka Raya - Natalia, Desi; Munte, Alfonso (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
This research examines the concept of